DEVELOPMENT OF ANIMATION VIDEOS IN SCIENCE LEARNING FOR STUDENTS OF GRADE IV SD - Wina Mariana Parinduri; Titin Rahmayanti Rambe; Renni Ramadhani Lubis (Universitas Negeri Medan, 2025)
This study aims to develop animated videos. The type of research used in this study is research and development (R&D). This study uses the 4-D development model (Four D). This model was developed by Sivasailam Thiagarajan, Dorothy S. Semmel, and Melyn I Semmel (1974). The development of the 4-D model consists of 4 stages, namely, define, design, development and disseminate. (Thiaagarajan, 1974). The research was conducted at SDN 026560 Binjai. This research was conducted in the even semester of the 2024/2025 school year. The subjects in the study were validators and grade IV students ofSDN 026560 Binjai. The object of this study was animated videos. Data collection techniques used were observation, questionnaires and tests. Based on the results of the study, it is known that Based on the validation results by material experts with a percentage of 89.90% it is categorized as very feasible, language experts with a percentage of 91.20%, and media experts with a percentage of 93.65% are categorized as very feasible. So, it can be concluded that animated videos are very feasible to be used for grade IV students at SDN 026560 Binjai.